Playing Nature: Ecology in Video Games, Alenda Y. Chang (2019). Issue 2 (1st June 2021) - Henderson, Brian
Review of: Playing Nature: Ecology in Video Games, Alenda Y. Chang (2019)Minneapolis, MN: University of Minnesota Press, 294 pp., ISBN: 978-1-5179-0632-0, p/bk, $27.00